Urgensi Peningkatan Kapasitas Pengelolaan Keuangan Daerah di Era Desentralisasi - Bambang Sunaryo; Celly Cicellia (Jurnal Bina Praja: Journal of Home Affairs Governance, 2014)
AbstrakPeningkatan kapasitas pengelolaan keuangan daerah menjadi hal yang sangat penting di era desentralisasi. Pengelolaan pajak parkir yang sekilas terlihat sebagai ranah kebijakan prosedural administratif, tidak pernah bisa lepas dari berbagai patologi yang sangat problematik bagi pengelolaan keuangan daerah. Kecamatan Banguntapan dipilih sebagai unit analisis dalam penelitian ini untuk merepresentasikan permasalahan pengelolaan pajak parkir di wilayah sub urban Kabupaten Bantul. Hal ini dikarenakan kharakteristik kewilayahan Bantul sebagai daerah sub urban dapat dilihat dari kharakteristik peri urban yang ada di Kecamatan Banguntapan. Selain itu, Kecamatan Banguntapan merupakan satu-satunya wilayah di Kabupaten Bantul yang memiliki subyek pajak parkir bertarif self assessment dan flat sehingga dinamika problema manajerial keuangan daerah dapat diobservasi dan dianalisis lebih mendalam di Kecamatan Banguntapan ini untuk melihat komparasi 2 sistem pemungutan pajak parkirtersebut. AbstractCapacity building of local finance management becomes important on decentralizations era. Empirically this research is aim to show that the parking tax management at glance seen as an administrative- procedural policy domain cannot release from phenomena on the existence of problematic pathology for regional financial management. District of Bantul Banguntapan characteristic as its suburbs form themain attractionin the selection of research because of the generallocus in sub-urbanarea, began to metamorphose into a parking tax revenues fromregionsthat contribute to the area thoughnot as big financial contribution income tax parking tax in urban areas. The Banguntapan sub district was chosen as analysis unit in this research to represent the issue of parking tax management in sub urban area of Bantul. This was due to the characteristic of Bantul area as sub urban area that can be seen from the characteristics of sub urban in Banguntapan sub district. Moreover, the Banguntapan sub district is the only area in Bantul which has a parking tax subject that the cost is self assessment and flat thus the dynamic of local finance managing problems can be observed and in-depth analyzed in Banguntapan sub district to seek the comparison of those 2 parking tax collection systems.